2018
DOI: 10.1186/s12903-018-0620-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of the Arabic versions of GOHAI and OHIP-14 in patients with and without denture experience

Abstract: BackgroundThe assessment of oral heath related quality of life (OHRQoL) for complete denture wearers according to a participant’s subjective perception may provide an indication of the adaptive capacity of the individual. The aim of this study was to compare and assess the validation of two quality of life measures, the Oral Health Impact Profile-14 (OHIP-14) and Geriatric Oral Health Assessment Index (GOHAI), in patients with and without previous denture experience.MethodsA total of 69 elders (36 male and 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
12
0
3
Order By: Relevance
“…Furthermore, the participants who reported poorer self-perceived oral health and had fewer teeth tended to have lower scores in the GOHAI-SP. This finding from this new version of the GOHAI-SP confirms the instrument validity for OHQoL evaluation and is similar to the results of other studies [4,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the participants who reported poorer self-perceived oral health and had fewer teeth tended to have lower scores in the GOHAI-SP. This finding from this new version of the GOHAI-SP confirms the instrument validity for OHQoL evaluation and is similar to the results of other studies [4,[35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 91%
“…These aspects are not included in the GOHAI questionnaire, and there are few references in the literature to support this finding [32,[34][35][36][37][38][39][40]. Another concern about the GOHAI is that the combination of positive and negative items may make it difficult to be interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency of the translated questionnaire was explored using Chronbach's alpha and the reliability was calculated using the Intra class correlation (ICC). A paired ttest was performed to identify the differences between the readings after repeated administration of the assessment tool with a gap of 2 weeks [14].…”
Section: Reliability and Validity Statistics For A-ohatmentioning
confidence: 99%
“…OHIP-14 has been used in many elds of dentistry but, it is not so common within orthodontics: only one study recently assessed the perception of patients wearing vacuum-formed retainers using this tool (22), while other studies reported its use in orofacial pain patients (23,24), prosthodontic patients (25), periodontal patients (26). A systematic review and meta-analysis (27) concluded that OHIP-14 scores were signi cantly lower after receiving treatment for malocclusion and that individuals without malocclusion/orthodontic treatment need had scored lower compared to those with such a condition.…”
Section: Discussionmentioning
confidence: 99%